(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
In this scientific research, the effect of phytase and xylanase enzyme preparations on nutrient digestion, feed intake, feed conversion and growth performance in broiler chicks was studied. The experiment was conducted on broiler chicks aged 1–28 days. During the study, the chicks were divided into three groups: the control group was fed a standard diet, experimental group I was fed a diet supplemented with phytase (500 FTU/kg), and experimental group II was fed a diet supplemented with phytase (500 FTU/kg) and xylanase (200 mg/kg). According to the results of the study, live weight gain, nutrient digestion and feed efficiency improved in the groups that received enzyme preparations. In particular, when phytase and xylanase were used together, feed conversion decreased to 1.36 kg/kg, and feed efficiency increased significantly. In addition, protein and phosphorus digestibility indicators were also higher than in the control group. The results obtained showed that the use of enzyme preparations in broiler poultry farming is important for increasing economic efficiency and rational use of feed resources.